Analisis Kritik Sastra dengan Pendekatan Ekspresif pada Novel Hujan Karya Tere Liye - Yeremias Bardi; Katharina Woli Namang; Sabina Nona Arifka (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The research aims to analyze the novel Rain by Tere Liye using an expressive literary criticism approach. This approach focuses on how the author’s personal experiences, feelings, and ideas contained in the work are reflected in the characters, plot, and language style used in the novel. This research uses qualitative methods with text analysis techniques and literature study to understand the meaning and messages contained in the novel. The result of the analysis show that the novel Rain contains the author’s emotional expression through dialogue, characters and narrative structure, which reflects the author’s inner struggles and life experiences. This research provides deeper insight into how literary works can be a medium for the writer’s personal expression that is able to influence readers emotionally.